Existence and uniqueness theorems for pointwise-slant immersions in Sasakian space forms - Alhouiti, Noura (AIMS mathematics, 2023)
In this paper we derive the Existence and Uniqueness Theorems for pointwise slant immersions in Sasakian space forms which extend the Existence and Uniqueness Theorems for slant immersions in Sasakian space forms proved by Cabreizo et al in 2001.